2008
DOI: 10.1063/1.2903544
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index calculation using the structural properties of La4Ti9O24 glass

Abstract: Local structure origin of higher glass forming ability in Ta doped Co65B35 amorphous alloy J. Appl. Phys. 112, 073520 (2012) NMR and conductivity studies of the mixed glass former effect in lithium borophosphate glasses J. Chem. Phys. 137, 124507 (2012) Robust hydrophobic Fe-based amorphous coating by thermal spraying Appl. Phys. Lett. 101, 121603 (2012) Correlating local structure with inhomogeneous elastic deformation in a metallic glass A high refractive index of 2.231Ϯ 0.001 at 1313 nm is achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
5
39
1
1
Order By: Relevance
“…Masuno [5] found that the refractive index of BaTi 2 O 5 glass was 2.15, the Abbe number was 21.5, and the optical transmittance could be measured from 340 nm to 7.7 μm. Arai [17] demonstrated that the colorless and transparent spherical La 4 Ti 9 O 24 glass could be prepared by using an aerodynamic levitation furnace. The refractive index was 2.231 at 1313 nm and the theoretical calculations suggested that five-fold coordinated Ti-O clusters had played an important role in high refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Masuno [5] found that the refractive index of BaTi 2 O 5 glass was 2.15, the Abbe number was 21.5, and the optical transmittance could be measured from 340 nm to 7.7 μm. Arai [17] demonstrated that the colorless and transparent spherical La 4 Ti 9 O 24 glass could be prepared by using an aerodynamic levitation furnace. The refractive index was 2.231 at 1313 nm and the theoretical calculations suggested that five-fold coordinated Ti-O clusters had played an important role in high refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Containerless processing enables glass formation of materials with a low glass forming ability because it prevents heterogeneous nucleation from the container walls and thus promotes deeper undercooling of the melt. Some binary systems, such as Al 2 O 3 -based [7,8], TiO 2 -based [9][10][11][12][13], and Nb 2 O 5 -based glasses [14], have been vitrified in bulk form without the use of network-former oxides by utilizing containerless processing.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is useful for vitrifying materials in bulk form with low glass-forming ability. 15 The La 4 Ti 9 O 24 glass consists of~65% TiO 5 and~35% TiO 6 , 16 and it has a refractive index of 2.37 at 589 nm exceeding that of BaTi 2 O 5 . These glasses had unusual characteristic structures and remarkable optical properties.…”
Section: Introductionmentioning
confidence: 99%